2018
DOI: 10.1142/s0218001418570069
|View full text |Cite
|
Sign up to set email alerts
|

White Blood Cells Classification with Deep Convolutional Neural Networks

Abstract: The necessary step in the diagnosis of leukemia by the attending physician is to classify the white blood cells in the bone marrow, which requires the attending physician to have a wealth of clinical experience. Now the deep learning is very suitable for the study of image recognition classification, and the effect is not good enough to directly use some famous convolution neural network (CNN) models, such as AlexNet model, GoogleNet model, and VGGFace model. In this paper, we construct a new CNN model called … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 7 publications
0
20
1
1
Order By: Relevance
“…The dual-stage CNN architecture classified images into 10 types of myeloid and erythroid maturation series, and achieved excellent performance. Moreover, based on deep residual learning theory and medical domain knowledge, Qin et al [26, 27] presented a fine-grained leukocyte classification method for microscopic images. This proposed deep residual neural network was tested on microscopic image dataset with 40 leukocyte categories, and achieved desired results.…”
Section: Introductionmentioning
confidence: 99%
“…The dual-stage CNN architecture classified images into 10 types of myeloid and erythroid maturation series, and achieved excellent performance. Moreover, based on deep residual learning theory and medical domain knowledge, Qin et al [26, 27] presented a fine-grained leukocyte classification method for microscopic images. This proposed deep residual neural network was tested on microscopic image dataset with 40 leukocyte categories, and achieved desired results.…”
Section: Introductionmentioning
confidence: 99%
“…WBCNet's rate of convergence was faster, the training data fits better, and the accuracy was higher. Ultimately, the experiment concluded that WBCNet was overall better than the customary models [4].…”
Section: White Blood Cells Classification With Deep Convolutional mentioning
confidence: 99%
“…Суть технологии глубокого обучения заключается в том, что путь извлечения признаков не разрабатывается людьми, а изучается на основе данных с использованием процедуры обучения общего назначения. В области глубокого обучения, конволюционные нейронные сети (CNN [24][25][26][27][29][30], которая должна обеспечить наличие во входном изображении кандидатов на объекты по сегментации, а количество объектов не превышает одного за счет обрезки изображения вручную или сложного шага сегментации. Эти классификационно-задачные методы, как правило, направлены на распознавание пяти типов зрелых лейкоцитов, обычно встречающихся в периферической крови, и начинают классификацию с обрезанных формами лейкоцитов, что приводит к неудобствам в реальных приложениях.…”
Section: основная часть исследование технологий получения обработкиunclassified